Cognitive systems and the extended mind - Rupert, Robert D. (New York ; Oxford : Oxford University Press, 2009)
Robert Rupert argues against the view that human cognitive processes comprise elements beyond the boundary of the organism, developing a systems-based conception in place of this extended view.
Description based on print version record.
Keywords: Cognition; Cognitive science